Neutrophil Elastase Inhibitor Sivelestat Attenuates Myocardial Injury after Cardioplegic Arrest in Rat Hearts - Fujii, Masahiro (Ann Thorac Cardiovasc Surg, 2019)
Purpose: Sivelestat, a neutrophil elastase inhibitor, attenuates global ischemia-induced myocardial damage and coronary endothelial dysfunction. Here, we investigated whether sivelestat exerts the cardioprotective effects against cardioplegic arrest in rat hearts. Methods: Isolated Langendorff-perfused rat hearts were randomly allocated to three groups and subjected to 2-min infusions with St. Thomas’ Hospital cardioplegic solution No. 2 (STH2) and 30-min global ischemia followed by 60-min reperfusion as follows: (i) control (STH2 treatment only), (ii) sivelestat (19 μmol/L) infusion for the first 10 min of reperfusion, and (iii) sivelestat (19 μmol/L) infusion for 10 min before ischemia and for the first 10 min of reperfusion. Left ventricular developed pressure (LVDP) recovery and troponin T leakage were measured at the end of reperfusion. Coronary flow response to acetylcholine (ACh) was assessed. Results: Single and multiple doses of sivelestat significantly improved LVDP recovery (69 ± 15 and 69 ± 14 vs 48 ± 15 [control]; p <0.05) and decreased troponin T leakage (0.4 ± 0.3 and 0.7 ± 0.5 vs 1.7 ± 0.6 [control]; p <0.05). Multiple doses of sivelestat significantly improved coronary flow response to ACh (121 ± 9 vs 105 ± 4; p <0.05). Conclusions: Addition of sivelestat to STH2 attenuates myocardial injury after cardioplegic arrest in rat hearts. This cardioprotective effect was achieved even when sivelestat was administered during early reperfusion.